2019
DOI: 10.7600/jpfsm.8.173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of switching force control direction on consecutive compared to discrete adjustment

Abstract: We investigated the characteristics of consecutive adjustment focusing on the phase before relaxing completely compared to discrete adjustment that involves just relaxing completely. Eleven participants were instructed to produce an isometric knee extension force based on their maximum voluntary force (MVF), as quickly and accurately as possible. They conducted discrete and consecutive tasks. For the discrete task, they were asked to relax their force completely from a starting level of 20% or 60% MVF. And for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…Previous studies that evaluated force control have suggested that the magnitude of prior force may influence the control of one's posterior force (Laabs, 1973). Although the present results appear to support those of Laabs (1973), a variety of factors, such as the size of the previous force, size of the required level, and size of the change amount, are associated with the history of force control and are involved in this process (e.g., Spiegel et al, 1996;Harbst et al, 2000;Ohtaka and Fujiwara, 2019). It has been shown that changing one's timing has a greater effect on motor control than changing the magnitude of one's force (Rinkenauer et al, 2001).…”
Section: Discussioncontrasting
confidence: 62%
“…Previous studies that evaluated force control have suggested that the magnitude of prior force may influence the control of one's posterior force (Laabs, 1973). Although the present results appear to support those of Laabs (1973), a variety of factors, such as the size of the previous force, size of the required level, and size of the change amount, are associated with the history of force control and are involved in this process (e.g., Spiegel et al, 1996;Harbst et al, 2000;Ohtaka and Fujiwara, 2019). It has been shown that changing one's timing has a greater effect on motor control than changing the magnitude of one's force (Rinkenauer et al, 2001).…”
Section: Discussioncontrasting
confidence: 62%